Sixth Five Year Plan 1980-85 Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1980)
It was but natural that economic planning should have been introduced in Goa, Daman and Diu in 1962-63, i.e. immediately after the territory’s liberation from the alien rule. By that time, two and a half Five Year Plans had already been implemented in the rest of the country. The first plan of this territory was actually a three-year plan coinciding with the last three years of the country’s Third Five Year Plan (1961-66). This was followed by three Annual Plans before the introduction of the Fourth Five Year Plan in April, 1969. the Fifth Five Year Plan (1974-79) came into force in April, 1974, and was supposed to have run the full five year period, up to March, 1979.
Union Territory of Goa, Daman and Diu